Investigation of Sound Transmission Loss Through Sandwich Panel with Foam Core (Journal of University of Babylon for Engineering Sciences, 2018)
In the past years, customer and consumer request are increased for performance sound. Where vibration and noise characteristics are made of important design criteria. The vibro- acoustic behavior is considered in the composite sandwich, important research topic to provide a suitable design with consumer requirements.The sound intensity method is widely using to measure the sound transmission loss between two rooms. This method are used with a composite materials, that are consist of two steel layers between them one layer for core. This paper provides a brief description of the sound intensity method and it is depended on ISO140[1]. Finite Element Method (FEM) are used to comparison with experimental results.The core of different thickness was used to study its effect on acoustic insulation. The experimental and theoretical results are shown, that the value of sound transmission loss are increased by rates of 6dB when the core thickness is doubled .